Multistage Surgical Treatment of Multisystem Closed Abdominal Trauma: Standardization of the Approach - S. S. Maskin; V. V. Aleksandrov; V. V. Matyukhin; M. I. Parovatkin (Неотложная медицинская помощь, 2021)
Introduction. The multisystem closed abdominal trauma is accompanied by a high mortality rate, and exceeding the minimum required volume of surgery in an extremely difficult patient’s condition often leads to an unfavorable outcome.Aim of study. Standardization of staged treatment of patients with severe concomitant closed abdominal trauma.Material and methods. This review presents the latest information obtained as a result of studying domestic and foreign literature on the issue of multistage surgical treatment of severe multisystem closed abdominal trauma. The concept of damage control, its stages are described step by step, indications for types of surgical interventions are specified. The literature data on the results of clinical application of the technique from the standpoint of evidence-based medicine are presented.Conclusion. A clear knowledge of the required volume of surgical intervention at each stage of treatment of patients with severe concomitant closed abdominal trauma, the main points of intensive care, the criteria for patient stabilization and indications for relaparotomy improve the treatment results for this category of victims.